Prevalence of Coronary Microvascular Dysfunction in Patients after Coronary Artery Bypass Grafting - Marushko, Yevhen Yu.; Stychynskyi, Oleksandr S. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To analyze the prevalence of coronary microvascular dysfunction (CMD) in patients with coronary artery disease after coronary artery bypass grafting (CABG). Materials and methods. The study was conducted in compliance with the provisions of the Declaration of Helsinki and was approved by the local ethics committee during 2018-2021. Due to recurrent complaints of discomfort/pain behind the sternum or shortness of breath during physical exertion in patients after CABG (average time of occurrence 18 ± 6 months after surgery), as well as positive or doubtful result of the stress testing, 31 patients were re-hospitalized for further examination. To diagnose CMD, echocardiography was performed with intravenous dipyridamole in order to determine the coronary flow reserve. The patency of the grafts was confirmed and newly formed hemodynamically significant coronary artery lesions were excluded during invasive coronary angiography. Results. The mean age was 61.2 ± 2.3 years, the majority of the patients were male (20 [64.5%]). The most common comorbid pathologies in the patients were: hypertension in 29 patients (93.5%), impaired glucose metabolism (diabetes/prediabetes) in 17 (54.8%) subjects, 13 (41.9%) patients had a history of myocardial infarction. Left ventricular ejection fraction according to echocardiography was reduced (less than 55%) in 5 (16.1%) of 31 patients, in others it was preserved. After CABG, there was a trend towards the coronary flow reserve increase, but no significant difference was found (1.89 ± 0.08 vs. 2.11 ± 0.13; p > 0.05). The presence of CMD before and after CABG did not change significantly (13 [41.9%] vs. 12 [38.7%]; p > 0.05). Conclusion. According to the results of the study, CMD is a common pathology in patients with obstructive coronary artery disease and is found in about 40% of patients with repeated myocardial ischemia after CABG. CABG did not affect the frequency of detection of CMD in patients with coronary artery disease before and after the operation.